Back Cover: Electron‐Deficient Heteroacenes that Contain Two Boron Atoms: Near‐Infrared Fluorescence Based on a Push–Pull Effect (Angew. Chem. Int. Ed. 40/2021). Issue 40 (12th July 2021) - Ito, Masato; Sakai, Mika; Ando, Naoki; Yamaguchi, Shigehiro
Abstract : An effective strategy to endow an acene skeleton with near‐infrared (NIR) emission properties is reported by Shigehiro Yamaguchi and co‐workers in their Research Article on page 21853 . The incorporation of boron and oxygen atoms furnishes a push–pull structure along the periphery of the acene skeleton. In particular, a thienothiophene‐based diboraheteroacene exhibits a sharp NIR emission band with a narrow band width.